2011
DOI: 10.1603/ec10419
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Susceptibility of Cnaphalocrocis medinalis (Lepidoptera: Pyralidae) in China

Abstract: Insecticide control is the major measure for suppression of Cnaphalocrocis medinalis (Guenée) (Lepidoptera: Pyralidae) damage, and a few insecticides used for long time have proved to fail to control this pest in China. Several new chemicals have been introduced for control of C. medinalis. However, there was no baseline susceptibility data of C. medinalis to insecticides used or will be in use. In this study, a seedling dipping method was developed for bioassay of insecticide susceptibility of C. medinalis. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 26 publications
1
29
0
1
Order By: Relevance
“…Therefore, the fourth-instar larval midgut was selected as the target tissue for insecticide exposure. In previous studies, the organophosphate insecticide chlorpyrifos has been effectively used for the control of a wide range of pests, including Chilo suppressalis , planthoppers and C. medinalis (Zheng et al 2011, Zhang et al 2014). The expression of the four genes was compared between chlorpyrifos-treated and untreated control insects.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the fourth-instar larval midgut was selected as the target tissue for insecticide exposure. In previous studies, the organophosphate insecticide chlorpyrifos has been effectively used for the control of a wide range of pests, including Chilo suppressalis , planthoppers and C. medinalis (Zheng et al 2011, Zhang et al 2014). The expression of the four genes was compared between chlorpyrifos-treated and untreated control insects.…”
Section: Resultsmentioning
confidence: 99%
“…Narrow variations in chlorantraniliprole susceptibility (based on LC 50 ) were observed in Þeld populations of P. xylostella (Þvefold) (Wang et al 2010), Choristoneura rosaceana (5.3-fold) (Sial et al 2010), Cnaphalocrocis medinalis (5.8-fold) (Zheng et al 2011), Chilo suppressalis (9.4-fold) (Huang et al 2011), Spodoptera exigua (sixfold) , and Bemisia tabaci (Þvefold) (Li et al 2012). Limited variation of chlorantraniliprole susceptibility in pest Þeld populations suggested that there is no cross-resistance to chlorantraniliprole conferred by resistance to currently used insecticides (Wang et al 2010, Li et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorpyrifos was the main insecticide for control of Asiatic rice stem borer (Chilo suppressalis [Walker]; Crambidae) and rice leaf-folder (Cnaphalocrocis medinalis [Guinée]; Crambidae) in China for yr (He et al 2008;Zheng et al 2011), and was also intensively used to control the rice planthopper. Fukuda & Nagata (1969) reported great differences in susceptibility to organophosphorus insecticides among geographic populations of WBPH.…”
Section: Discussionmentioning
confidence: 99%